Service quality and relationship with UUM students satisfaction: a study at Pizza Hut V-mall UUM - Bahuridin, Syahidahtul Nadia; Ahmad, Mohd Akhir (2019)
The purpose of this study is to observe whether the service quality offered by the Pizza Hut at V-mall UUM meets the UUM student’s satisfaction. There are two main objectives of this study which are to investigate the relationship between service quality and student satisfaction and to identify the most influence service quality variables on student satisfaction. Service quality is consisting of five sub-dimensions: (1) Reliability, (2) Assurance, (3) Tangible, (4) Empathy and (5) Responsiveness. This research was adapting the SERVQUAL dimension. A quantitative approach was used to measure the relationship between the dependent variable and independent variables. The samples in this study were the students from University Utara Malaysia. The data were analyzed by using Statistical Package for Social Sciences (SPSS) software to obtain descriptive statistics.